Antiapoptosis effect of ZiShen prescription to increase learning and memory abilities of compound Alzheimer's disease model rats. Issue 7 (20th February 2019) - Wei, Zhiqiang; Zhang, Yu; Chen, Yan; Xia, Xiaoshuang; Zheng, Boyu; Sun, Xugang; Zhang, Guangming; Wang, Ling; Zhang, Qi; Xu, Chen; Jiang, Shihe; Li, Xiulian; et al.
Abstract: Alzheimer's disease (AD) is a neurodegenerative disease characterized progressive memory loss and cognitive impairment. In previous studies, the activities of extracts of Chinese medicinal herbs to treat brain function disorders caused by AD have already been reported. ZiShen prescription was a traditional Chinese medicine (TCM) compound prescription reformed for AD disease based on the basic theory of TCM. To explore the effect of ZiShen (kidney‐reinforcing) prescription on the learning and memory abilities, we made compound AD model rats by injecting d ‐galactose and ibotenic acid into the abdominal cavity to damage both sides of the nucleus basalis of Meynert with ibotenic acid. The trisected Y‐maze was used to test the learning and memory abilities of AD model rats before and after treatment by ZiShen prescription and Piracetam. To investigate the mechanism of ZiShen prescription, the expressions of apoptosis‐related genes (Bcl‐2/Bax) in the cortex and hippocampus of compound AD model rats were detected in the cortex and hippocampus. The results show that, comparing with Piracetam, a clinical medicine to promote the thinking and memory for AD patients, ZiShen prescription significantly increased the learning and memory abilities of the compound AD model rats. After the treatment of ZiShen prescription, the expression of Bcl‐2 was upregulated, along with a downregulation of Bax in the cortex and hippocampus of compound AD model rats. And the results indicated that the clinical benefits of ZiShen prescription were slightly better than Piracetam. Still, further well‐designed studies are required to ensure the clinical effect of ZiShen. Abstract : ZiShen increased the learning and memory abilities of the compound Alzheimer's disease (AD) model rats. After the treatment of ZiShen, the expression of Bcl‐2 was upregulated and the expression of Bax was downregulated. The clinical benefits of ZiShen prescription were slightly better than Piracetam.